Hybrid HVDC circuit breaker with self‐powered gate drives. Issue 2 (1st February 2016) - Effah, Francis B.; Watson, Alan J.; Ji, Chao; Amankwah, Emmanuel; Johnson, C. Mark; Davidson, Colin; Clare, Jon
Abstract : The ever increasing electric power demand and the advent of renewable energy sources have revived the interest in high‐voltage direct current (HVDC) multi‐terminal networks. However, the absence of a suitable circuit breaker (CB) or fault tolerant voltage source converter station topologies with the required characteristics (such as operating speed) have, until recently, been an obstacle in the development of large scale multi‐terminal networks for HVDC. This study presents a hybrid HVDC CB concept which is capable of meeting the requirements of HVDC networks. Simulation results are presented which are validated by experimental results taken from a 2.5 kV, 700 A rated laboratory prototype.